Penetapan Kadar Sari Larut Air dan Kadar Sari Larut Etanol Simplisia Buah Tin (Ficus carica L.) - Nabila Nur Latifa; Lanny Mulqie; Siti Hazar (UNISBA Press, 2022)
Abstract. Fig fruits (Ficus carica L.) is one of the plants found in the Al-Quran Surah At-tin have many function as medicine. Raw material of fig fruit (Ficus carica L.) need to be standardized as one of the important stages in development of Indonesian medicine. Standardization of the simplicia of fig fruits (Ficus carica L.) was tested for water soluble extract content and ethanol soluble extract content to determine the amount of compound content in simplicial that can be attracted by solvent. A simplicia cannot be said to be of good quality if it does not meet the quality requirements stated in the simplicia monograph. However, the requirements for the standardization of the simplicia of fig fruits have not been listed in the general monograph. The purpose of this research was to determine of the water soluble extract content and ethanol soluble extract content of the simplicia of fig fruits (Ficus carica L.). The method used in this research is experimental at the Laboratory of the Islamic University of Bandung. Based on the results simplicia standardization of fig fruits (Ficus carica L.) water soluble extract content of 3.70% and ethanol soluble extract content of 39.25%. Abstrak. Buah Tin (Ficus carica L.) merupakan salah satu tanaman yang terdapat di dalam Al- Quran Surat At-tin yang memiliki banyak manfaat dalam pengobatan. Bahan baku buah Tin (Ficus carica L.) perlu dilakukan standardisasi sebagai salah satu tahapan dalam pengembangan obat di Indonesia. Standardisasi simplisia buah Tin (Ficus carica L.) dilakukan uji kadar sari larut air dan kadar sari larut etanol untuk mengetahui jumlah kandungan senyawa dalam simplisia yang dapat tertarik oleh pelarut. Suatu simplisia tidak dapat dikatakan bermutu jika tidak memenuhi persyaratan mutu yang tertera dalam monografi simplisia. Namun, persyaratan kadar sari larut air dan etanol simplisia buah Tin belum tercantum dalam monografi umum. Tujuan penelitian ini adalah untuk mengetahui penetapan uji kadar sari larut air dan kadar sari larut etanol simplisia buah Tin (Ficus carica L.). Metode yang digunakan pada penelitian ini adalah secara eksperimental di Laboratorium Universitas Islam Bandung. Berdasarkan hasil standardisasi simplisia buah Tin (Ficus carica L.) maka diperoleh kadar sari larut air sebesar 3,70% dan kadar sari larut etanol sebesar 39,25%.